Sustainable Structures and Buildings (Cham Springer Nature, 2024)
This open access book includes detail on various structures, buildings, and building materials from different structural and sustainability perspectives. It describes how the building industry is vital for the achievement of the sustainable development goals, namely, economic growth, social progress, and the effective protection of the environment. The aim of this collection is to foster the design and construction of sustainable structures and buildings to reduce the environmental load, connect with the environment, and benefit the health of occupants. Presenting the knowledge, trends, and developments from a group of contributors in the field working with different kinds of structures, structural components, buildings, and building materials, the book is ideal for practitioners working in commercial settings, as well as engineering students and researchers concerned with sustainability issues.
English
Keywords: Building construction & materials; Environmentally-friendly architecture & design; Materials science; Sustainability